Bioengineering potato plants to produce benzylglucosinolate for improved broad-spectrum pest and disease resistance - González Romero, M.E.; Rivera, C.; Cancino, K.; Geu-Flores, F.; Cosio, E.G.; Ghislain, M.; Halkier, B.A. (Springer, 2021)
In traditional, small-scale agriculture in the Andes, potatoes are frequently co-cultivated with the Andean edible tuber Tropaeolum tuberosum, commonly known as mashua, which is believed to exert a pest and disease protective role due to its content of the phenylalanine-derived benzylglucosinolate (BGLS). We bioengineered the production of BGLS in potato by consecutive generation of stable transgenic events with two polycistronic constructs encoding for expression of six BGLS biosynthetic genes from Arabidopsis thaliana. First, we integrated a polycistronic construct coding for the last three genes of the pathway (SUR1, UGT74B1 and SOT16) into potato driven by the cauliflower mosaic virus 35S promoter. After identifying the single-insertion transgenic event with the highest transgene expression, we stacked a second polycistronic construct coding for the first three genes in the pathway (CYP79A2, CYP83B1 and GGP1) driven by the leaf-specific promoter of the rubisco small subunit from chrysanthemum. We obtained transgenic events producing as high as 5.18 pmol BGLS/mg fresh weight compared to the non-transgenic potato plant producing undetectable levels of BGLS. Preliminary bioassays suggest a possible activity against Phytophthora infestans, causing the late blight disease and Premnotrypes suturicallus, referred to as the Andean potato weevil. However, we observed altered leaf morphology, abnormally thick and curlier leaves, reduced growth and tuber production in five out of ten selected transgenic events, which indicates that the expression of BGLS biosynthetic genes has an undesirable impact on the potato. Optimization of the expression of the BGLS biosynthetic pathway in potato is required to avoid alterations of plant development.Graphical abstract